Detection of Compounds and Efficacy of N-Butanol Stem Extract of Chenopodium Murale L. Against Fusarium Oxysporum F.SP. Lycopersici (Bangladesh Journal of Botany, 2022)
An in vitro study was conducted to assess the antifungal efficacy and potential antifungal compounds of n-butanol fraction of methanolic stem extract of Chenopodium murale L. against Fusarium oxysporum f. sp. lycopersici. In order to get n-butanolic fraction, the methanolic extract was partitioned using n-hexane, chloroform and ethyl acetate to separate non-polar and low polarity compounds. Finally, n-butanol fraction was separated and its 8 concentrations ranging from 1.562 to 200 mg/ml were assessed for antifungal activity against F. oxysporum f. sp. lycopersici. There was 1 to 100% reduction in biomass of F. oxysporum f. sp. lycopersici due to these concentrations. GC-MS analysis of n-butanol fraction showed 25 compounds in it. Literature survey showed that among the identified compounds, 10 showed antifungal activities against different fungi. These antifungal compounds included 2-heptanol, 1-hexanol, 2-hexanol, 3-hexanol, 1- nonyne, decane, tridecane, palmitic acid, 3-octanone and β-sitosterol, could be responsible for antifungal activity against F. oxysporum f. sp. lycopersici in the present study.Bangladesh J. Bot. 51(4): 663-668, 2022 (December)